1999
DOI: 10.1002/(sici)1097-0215(19990702)82:1<77::aid-ijc14>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Human breast-cancer metastasis formation in a nude-mouse model: Studies of hyaluronidase, hyaluronan and hyaluronan-binding sites in metastatic cells

Abstract: Few animal models are available to study metastasis formation. The purpose of the present study was to obtain a useful model of metastasis formation in nude mice in an attempt to analyze the stroma reaction and in particular the production and the expression of hyaluronan (HA), hyaluronidase, and HA‐binding sites by cultivated cells, and HA and hyaluronectin (HN) in the invasive areas of tumors. Nude mice were subjected to i.p. injections of several human cancer cell lines (PLC/PRF/5, HepG2, CB 191, CB 193, PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 17 publications
2
35
0
Order By: Relevance
“…In these situations, hyal-1 expression was frequently upregulated in the xenografts. This has been previously observed with the CAL51 cell line, 42 where it is suggested that the increase in hyal-1 expression plays a role in extravasation and metastasis. In addition it was recently shown by immunohistochemistry that hyal-1 has a stromal and epithelial pattern of staining that increased with prostate cancer grade and metastasis.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In these situations, hyal-1 expression was frequently upregulated in the xenografts. This has been previously observed with the CAL51 cell line, 42 where it is suggested that the increase in hyal-1 expression plays a role in extravasation and metastasis. In addition it was recently shown by immunohistochemistry that hyal-1 has a stromal and epithelial pattern of staining that increased with prostate cancer grade and metastasis.…”
Section: Discussionsupporting
confidence: 70%
“…No increase was seen in the incidence, number, or size of tumor nodules across a range of sites after 80 days for the hyal-1 overexpressing cell line (data not shown). Interestingly, Victor et al 42 showed metastasis in nude mice after i.p. CAL51 administration and in addition the transition of these cells from the primary to the metastatic state was characterized by increased HA and hyaluronidase production.…”
Section: In Vitro and In Vivo Studies With Hyal-1 Overexpressing Cellmentioning
confidence: 99%
“…On the other hand, VEGF secretion can enhance distant metastasis, but metastasis formation also depends on the stroma reaction and cell type. That we did not see metastasis in the animal model might be because the microenvironment is not damaged by radiotherapy and the HepG2 cell line is nonmetastatic in nude mice (47). However, we did note that radiotherapy promoted both intrahepatic and extrahepatic tumor progression in hepatocellular carcinoma patients.…”
Section: Discussionmentioning
confidence: 63%
“…Contrarily, Victor et al showed that passage of a human breast cancer line CAL 51 from the primary state to metastatic stage increases hyaluronidase production (39). Expression of HYAL1 in a prostate cancer line that produces little hyaluronidase did not affect tumor growth but caused a slight increase in lung metastasis (40).…”
Section: Introductionmentioning
confidence: 99%